Location based reminder using geofencing / Nurul Husnina Husain - Husain, Nurul Husnina (Faculty of Computer and Mathematical Sciences, 2015)
Reminder applications are becoming the must have applications on mobile devices as it can help users to remind themselves on a specific task that must be accomplished. Nowadays, reminder applications become more effective and gain its popularity as it can ease the users in their daily life. Currently, most of the reminders are triggered by time which is not really appropriate as the users do not know when they will be at that location. By solving this problem, reminder based location can be used as most of the mobile devices have localization sensors which can make reminder have additional functionality. The location-based reminder will combine time-based and location-based as it will only alert if the reminder satisfy with both conditions. The reminder triggered only when the user is in the radius of location and geofencing is used to track a user’s current location. Geofencing technology uses GPS to track location in the 1000 metres. Besides, the location based reminder also will have additional features which are able to alert for enabling GPS and have snooze time.